The Issues of Word Choice in Fiction Translation - Khudoyorovich, Khamidov Khayrulla (International Journal of Psychosocial Rehabilitation, 2020)
Today, Uzbek literature can be considered one of the most developed and unique in Central Asia. It is a unique phenomenon in the region, the uniqueness of which is explained by the fact that the country is geographically in the heart of Asia, and genetically belongs to the Islamic cultural traditions. Indeed, the translation of the masterpieces of our literature into foreign languages and their worthy place in the treasury of world literature is of special importance today. At the same time, it is difficult to say that at present the translation of works of art from Uzbek into foreign languages is carried out sufficiently. The rich Uzbek culture reflected in the works of art remains a mystery to foreign readers. However, the growing interest of our literature lovers in the rich culture of the Uzbek people, in our classical and modern literature, shows that there is a serious need for the translation of samples of our literature. The issues of scientific study of the problems related to the translation of literary texts and the verification of published translations remain relevant. In the texts of fiction or poetry, language is not only a means of conveying information, but also a means of its artistic reproduction, conveying the aesthetic value of the work. In addition, the literary text is also a source of information about foreign culture. The value of comparative translation studies is that they make a significant contribution to the development of specific translation theories within specific language pairs. This article is devoted to the study of the theoretical aspects of the problems associated with word choice in literary translation, in which the main focus is on the views of foreign and Uzbek translators on this topic. Some of the comments and conclusions made in the article may be useful to the creators in the future translation process.